EVOLUCION EN LAS CONCEPCIONES SOBRE EVALUACION EN ESTUDIANTES DEL PROGRAMA DE MAESTRIA EN DOCENCIA DE LA QUÍMICA - Salcedo, Luis E.; Reyes, Lilia; Perafán, Andrés (Tecné, Episteme y Didaxis: TED, 2002)
ln this article we present the results of the application of a pedagogyca/ strategy to chemistry tea chers. This strategy was cre ated ¡n order to permit the refiection upon the issues of evaluation in theory and practice. ln this way, we can crea te real alternatives for transformation which contribute to an improvement of the qualíty of chemical education. Teachers are ab/e to change their perception of evaluation from a final accumulative proccess which centers attention only on the student to a concept of evaluation as a means of learning and improving the proccess of teaching. Through this strategy the teachers apply this vision to the development of chemical subjects based on a series of activities centered on problematic situations which evaluate throughout the proccess favoring a significant adquizition of chemistry